Technical and physical determinants of soccer match-play performance in elite youth soccer players - Rowat, O.; Fenner,J.; Unithan,V. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The aim of this study was to evaluate whether physical performance characteristics could be a better predictor than technical skills in determining the technical level of county soccer players in a match situation.